Psychological traits associated with anabolic androgenic steroid use and dependence: an exploratory cross-sectional study among female athletes - Morgan Scarth; Ingrid Amalia Havnes; Marie Lindvik Jørstad; Astrid Bjørnebekk (BMC Women's Health)
Abstract Background Anabolic–androgenic steroids (AAS) are commonly taken to increase muscle size and enhance performance. However, AAS can lead to many adverse effects, including challenges with mental health and behavior. This study aims to identify behavioral and psychological correlates of AAS use, and explore associations with dependence symptoms among female weightlifters. Methods A sample of n = 32 female weightlifters, including 16 with reported AAS use completed questionnaires including the Achenbach System of Empirically Based Assessment (ASEBA) and Buss-Perry Aggression Questionnaire (BPAQ). AAS dependence was evaluated using the Structure Clinical Interview for DSM-IV. Group comparisons were made using Welch’s t-tests between control and AAS groups, and AAS dependent and non-dependent groups. Exploratory correlation analyses were computed between symptoms of dependence and behavioral and psychiatric scales. Results Females who had used AAS had higher levels of both externalizing and internalizing psychopathology, including antisocial and attention problems, as well as aggressive traits. The most prevalent dependence symptoms were time spent on activities surrounding AAS use (n = 7, 50%), and using more or for longer than planned (n = 6, 42.9%). Dependence symptoms were associated with several ASEBA scales: tolerance was correlated with aggressive behavior (ρ = 0.79, p < 0.001), withdrawal was correlated with attention problems (ρ = 0.78, p < 0.001), and being unable to quit use was associated with anxious/depressive (ρ = 0.80, p < 0.001) and internalizing problems (ρ = 0.79, p < 0.001). Conclusions Females who currently or previously used AAS demonstrated significantly more difficulties with maladaptive functioning and aggressive traits compared to those who have never used. Attention problems and aggressive behavior were also associated with symptoms of AAS dependence, though longitudinal studies are required to determine the direction of this relationship.